Juvenile Justice practice : - Rodney, A. Ellis (Thomson Wadsworth, 2001)
This book provides information and skill-building exercises across a range of practice never before covered in a single text. Its breadth provides the new or aspiring practitioner with a solid, comprehensive foundation for future work. The authors offer workable solutions to many of the real-life situations face by professionals in their daily lives. Although the book is extremely current in its inclusion of today's most effective techniques and interventions, the authors have built into the book a focus on teaching students methods of staying current on the latest effective intervention and trends within the system.